2016
DOI: 10.3390/nu8090522
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Mediterranean Oriented Culture-Specific Semi-Quantitative Food Frequency Questionnaire

Abstract: The objectives were to develop a Mediterranean oriented semi-quantitative food frequency questionnaire (FFQ) and evaluate its validity in measuring energy and nutrient intakes. For FFQ development, the main challenge was to merge food items and practices reflecting cultural Mediterranean preferences with other food choices ensuing from diet transition to more westernized dietary patterns. FFQ validity was evaluated by comparing nutrient intakes against the average of two 24-h dietary recalls for 179 pregnant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
42
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 91 publications
(145 reference statements)
10
42
2
Order By: Relevance
“…Analyses at the nutrient level showed that intakes were significantly higher (P < 0.05) with the FFQ than with the WDR for most nutrients. These results are similar to the observations of other researchers [20,22,24,27,[31][32][33]. The overestimation of the FFQ can be associated to the use of 24-hour recall as a reference dietary method related to correlated errors of bias memories in the both methods [34].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Analyses at the nutrient level showed that intakes were significantly higher (P < 0.05) with the FFQ than with the WDR for most nutrients. These results are similar to the observations of other researchers [20,22,24,27,[31][32][33]. The overestimation of the FFQ can be associated to the use of 24-hour recall as a reference dietary method related to correlated errors of bias memories in the both methods [34].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, for all nutrients, the median percentage of participants correctly classified in the same third by both the food frequency questionnaire and the WDR range from 59% to 75% in men (median 64%), and from 54% to 70% in women (median 59%). According to Lombard et al [27], our participant's classification in the in same tertile/quartile was good ≥ 50% for nutrients and comparable to other studies [20,22,23,31].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Adherence to the MD is a multidimensional nutritional approach, as it involves not only dietary patterns but also lifestyle, sociocultural, cultural heritage, and environmental aspects [16]. Moreover, food dietary patterns are a major environmental factor and people are exposed to them numerous times every day during their lifetimes.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were instructed to self-complete two CMST at an interval of 2 weeks apart to assess test-retest reliability of the FFQ. A repeat administration time of 2 weeks was selected based on similar validation studies (29)(30)(31) and from a review highlighting that correlations were higher when repeat administrations of FFQ were 1 month or less apart, compared with 6-12 months (11) .…”
Section: Test-retest Reliability Assessmentmentioning
confidence: 99%